Penanaman Nilai-Nilai Moderasi Beragama Melalui Pendidikan Agama Islam dan Budi Pekerti Peserta Didik Kelas VIII di SMP Negeri 2 Kabupaten Bulukumba - Tanti Kurniasari; Andi Achrul; Syamsyuddin Syamsyuddin; Muzakkir Muzakkir; Muh. Rusdi. T. (Academia Open, 2025)
General Background: Indonesia’s rich cultural and religious diversity presents both a valuable asset and a potential source of social tension. Specific Background: Increasing cases of intolerance among students underscore the urgency of embedding religious moderation values through education. Knowledge Gap: Prior studies have largely focused on high school and university levels, with limited exploration at the junior high school level, especially in local contexts such as Bulukumba. Aims: This study aims to investigate how religious moderation values are instilled through Islamic Religious Education (PAI) and Character Education at SMP Negeri 2 Bulukumba. Results: Using a qualitative case study approach, findings show that values like tolerance, justice, openness, respect for differences, harmony, and rejection of extremism are integrated effectively into classroom teaching and school culture, though challenged by students’ diverse backgrounds and social media influences. Novelty: The study highlights how local cultural values, such as siri’ and pangadereng, can be contextualized to support moderate Islamic education. Implications: These findings suggest the need for inclusive, context-sensitive pedagogical strategies to strengthen national resilience through character education grounded in religious moderation.Highlight : The cultivation of religious moderation values through PAI and Budi Pekerti increases students' tolerance and openness to religious and cultural differences. The main obstacles come from the influence of social media, differences in cultural backgrounds, and lack of parental support. Effective religious moderation education integrates the curriculum, teacher role models, and inclusive school activities. Keywords : Religious Moderation, Islamic Education, Character Formation, Student Tolerance, Inclusive Schooling